Spatial Development of the 1507–1510 Plague in Poland and Its Consequences. Kalisz District Case Study - Związek, Tomasz (Journal of Environmental Geography, 2020)
The article discusses the causes and effects of the plague which is said to have spread over many Polish towns in 1507. The focus is on its possible causes, related to the occurrence of droughts and floods in Central Europe in the late 15th and early 16th century. Available sources from the late mediaeval period have also been analysed for the recorded perceptions of the extreme climatic and weather conditions. Special attention has been paid to the issues of intensity and spatial distribution of the effects of the plague on the example of one district. The analysis covered a variety of issues such as settlement changes, prices of basic goods or even some pollen data. The main results of the study indicate that the climatic extremes at the turn of the 16th century exerted a long-term impact on the society and economy of the region. They also contributed to the abandonment of settlements on rural sites.